Effect of Indirect Taxes on Macroeconomic Stability in Nigeria: An Autoregressive Distributed Lag (Ardl) Approach - Fakunmoju, Segun (The Journal of Accounting and Management, 2022)
Achieving sound macroeconomic stability is one of the major priorities of economic regulators. Nigeria economy majorly built on oil revenue in which unpredictability nature of the oil sector might adversely affected macroeconomic stability thus there is need to diversified Nigeria economy. Indirect taxes serve as the diversification means of generating revenue for an economy but Nigeria as an economy characterized with challenges of high level of tax gap, mono-culture oil revenue generation and weak tax system thus created challenges of generating maximum indirect taxes revenue to finance means of achieving sound macroeconomic stability. The problem of poor indirect tax revenue generation has caused deterioration in Nigeria macroeconomic stability rate. The objective of the study was to examine the effect of indirect taxes (VAT) and (CED) on Nigeria macroeconomic stability via real gross domestic product in Nigeria. The study used expost facto research design with focused on RGDP, VAT, CED, interest rate and exchange rate in Nigeria within the period of 1995-2020. Autoregressive Distributed Lag (ARDL) method of analysis was employed while unit root test was carried out among study variables and results shown that there was mixed level of stationarity. Finding revealed that the short-run model indicated that CED, INT and EXR were major short-run determinants of Nigeria economic growth while VAT was not short-run determinants of economic growth. Also, finding established that long run estimates established that, VAT, CED and INT show positive signs, indicating they influence macroeconomic stability measure with RGDP positively while EXR has negative effect on macroeconomic stability via RGDP (Adj.R2 = 0.537, F-stat = 74.001, p<0.05). The study concluded that both in the short and long runs VAT, CED, INT and EXR affected Nigeria macroeconomic stability. The study recommended that for an economy to achieve macroeconomic stability, government should ensure that VAT, CED and INT are not highly charged on investors and consumers when buying products and services, acquiring raw materials from other countries, and seeking loan in the bank.